2011
DOI: 10.1016/j.jss.2009.04.022
|View full text |Cite
|
Sign up to set email alerts
|

A High Omega-3 Fatty Acid Diet Mitigates Murine Pancreatic Precancer Development

Abstract: Background-Diets containing omega-3 fat have been associated with decreased tumor development in the colon, breast, and prostate. We assessed the effects of a diet rich in omega-3 (ω-3) fat on the development of pancreatic precancer in elastase (EL)-Kras transgenic mice and examined the effect of an ω-3 fatty acid on pancreatic cancer cells in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 25 publications
(20 reference statements)
3
31
0
Order By: Relevance
“…Tumor-expressed granzyme B degrades ECM components and promotes cancer cell invasion 9. This study is supported by Strouch et al34 who showed that a high ω3-fatty acid diet mitigates murine pancreatic precancer development.…”
Section: Effect Of Docosahexaenoic Acid On Pancreatic Carcinogenesissupporting
confidence: 65%
“…Tumor-expressed granzyme B degrades ECM components and promotes cancer cell invasion 9. This study is supported by Strouch et al34 who showed that a high ω3-fatty acid diet mitigates murine pancreatic precancer development.…”
Section: Effect Of Docosahexaenoic Acid On Pancreatic Carcinogenesissupporting
confidence: 65%
“…A tentative explanation is that the stimulating effect of the n6PUFA-diet was derived from n6PUFAs other than those tested in the present study in vitro. When fish-oil-based n3PUFA diets were used in carcinogen-treated hamsters, pancreatic carcinogenesis was inhibited in some but not all studies [6][7][8]. Although flaxseed-based n3PUFA diets have not been used in pancreatic cancer models, they indeed inhibited non-pancreatic cancers [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…In flaxseed and in fish oil, n-3 polyunsaturated FAs (n3PUFAs) also contribute as principal FAs [1]. Previous studies have shown that increased FAs regulate pancreatic cancer [2][3][4][5][6][7][8]. For instance, diets rich in SFAs and n6PUFAs accelerate the process of pancreatic carcinogenesis in the animal, whereas HFDs made of fish oil and thus rich in n3PUFAs sometimes inhibit the carcinogenetic process [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the existence of an inverse associations between intake of omega-3 FAs and risk of pancreatic cancer was reported in a large population-based case-control study [146] and confirmed in an animal model represented by EL-K-ras mice fed with a high omega-3 FA diet (23 % menhaden oil) compared with age-matched EL-Kras mice fed standard chow (5 % fat). In the first group, the incidence, frequency, and proliferative index of pancreatic pre-cancer EL-Kras mice were reduced compared to the control group [147]. However, a systematic review previously published on the effect of omega-3 FAs on cancer risk in prospective cohort studies, denied the existence of convincing evidence about the association between omega-3 FAs and cancer incidence.…”
Section: Pancreatic Cancermentioning
confidence: 95%